PENGARUH NILAI TUKAR, DEBT TO EQUITY RATIO DAN RETURN ON EQUITY TERHADAP HARGA SAHAM - Eva Moranty; Bonifasius MH. Nainggolan (LPPM Universitas Asa Indonesia, 2016)
The purpose of the research is to know the exchange rate (1), debt to equity ratio (2) and return on equity (3) simultaneously or partially on The Banking Industry Stock Price from Indonesia Stock Exchange. The population of this research are the banking companies which are listed in Indonesia Stock Exchange (BEI) since 2011-2014. The sample that used for this research are 10 banks. This research use purposive sampling technique to get the sample. Data analysis tools that will be used for this research are multi linier regression, classic assumption test (normality test, runs test, heteroscedasticity test and multy collinearity test) whereas the hypothesis test including the F test, t test, partial correlation analysis and coefficient of determination ( ). The result of this research concluded that exchange rate, debt to equity ratio, and return on equity have effected stockprice of the bank companies, significantly, at the market of Indonesia Stock Exchange.